Förster resonant energy transfer from an inorganic quantum well to a molecular material: Unexplored aspects, losses, and implications to applications - Itskos, Grigorios; Othonos, Andreas; Choulis, Stelios A.; Iliopoulos, Eleftherios (My University, 2015)
A systematic investigation of Förster resonant energy transfer (FRET) is reported within a hybrid prototype structure based on nitride single quantum well (SQW) donors and light emitting polymer acceptors. Self-consistent Schrödinger-Poisson modeling and steady-state and time-resolved photoluminescence experiments were initially employed to investigate the influence of a wide structural parameter space on the emission quantum yield of the nitride component. The optimized SQW heterostructures were processed into hybrid structures with spin-casted overlayers of polyfluorenes. The influence of important unexplored aspects of the inorganic heterostructure such as SQW confinement, content, and doping on the dipole-dipole coupling was probed. Competing mechanisms to the FRET process associated with interfacial recombination and charge transfer have been studied and their implications to device applications exploiting FRET across heterointerfaces have been discussed.
Keywords: Light-emitting-diodes; Optical-excitations; Color-conversion; Organic material; Nanostructures; Devices; Surface; Efficiency; Overlayer; Emission